2010
DOI: 10.5251/abjna.2010.1.5.1044.1049
|View full text |Cite
|
Sign up to set email alerts
|

Study of sewage sludge use in agriculture and its effect on plant and soil

Abstract: The plant macro and micro nutrients as well as organic matter make sludge disposal in soil an attractive option. Nitrogen has received most attention and it is normally the most abundant sludge nutrient. One of the best alternatives to waste disposal is through the soil-plant system as a fertilizer. Based on properties different wastes can be co-recycled in order to take simultaneously the best profit and minimize environmental pollution .An experiment was carried out with a calcareous soil. Using six differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 13 publications
8
21
0
1
Order By: Relevance
“…This domestic effluent treatment also produces sewage sludge (SS) which is still up to now used as source of macro-and micronutrients for agricultural lands [1,2]. Land application of SS may have many beneficial effects because it improves soil physical properties and increases soil organic matter content which represents several advantages for crops production [2,3]. However, an excessive spreading also leads to a soil contamination with heavy metals (HMs) and/or with some organic pollutants usually contained in sludge.…”
Section: Introductionmentioning
confidence: 99%
“…This domestic effluent treatment also produces sewage sludge (SS) which is still up to now used as source of macro-and micronutrients for agricultural lands [1,2]. Land application of SS may have many beneficial effects because it improves soil physical properties and increases soil organic matter content which represents several advantages for crops production [2,3]. However, an excessive spreading also leads to a soil contamination with heavy metals (HMs) and/or with some organic pollutants usually contained in sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum uptake of nitrogen (27.85 kg ha -1 ) by grain was found with 125% RDF which was at par with 100% RDF. Ahmed et al, (2010) reported that the application of sewage sludge to the calcareous soil lowered the pH of the soil, although the value always around 7.75-7.9 at the end of the experiment. In the barley plants it was observed that the higher the yield, the higher the nitrogen contents.…”
Section: Uptake Of Nitrogen (Kg Ha -1 ) By Grain Of Ricementioning
confidence: 99%
“…Alternatively it is used in land reclamation, forestry, horticulture, landscaping, energy and resource recovery (Ahmed et al 2010). Recently, its usage in agriculture has been suggested as one of the eco-friendly option for its disposal (Singh and Agrawal 2010;Ríos et al 2012).…”
mentioning
confidence: 99%